Exploring Factors that Affect the Performance of Financial Intermediaries in the Insurance Sector - Cedrick Mathisa; Bibi Z. Chummun (E-Journal of Humanities, Arts and Social Sciences)
This article evaluates the prominent factors affecting financial intermediaries’ performance in the insurance industry. It is widely accepted that the performance of financial intermediaries in the insurance industry contributes to both industrial expansion and an increase in the market value of financial service providers. Surprisingly, there is not much research on financial intermediaries’ ability to identify obstacles that hinder their effectiveness. This study thus sought to provide strategies for financial services providers, insurance conglomerates, and senior management to gain a broad understanding and thorough review of the important influential factors that should be considered to enhance the performance of financial intermediaries in the insurance sector. To investigate the factors that enhance the performance of financial intermediaries, a close-ended questionnaire was developed in which 300 responses were collected at a market conduct authority. A quantitative approach was judiciously selected to analyse the data and identify the relationship between several factors. Using logistic regression models, key socioeconomic characteristics impacting the performance of financial intermediaries were identified including organisation, gender, education, level of education, and experience. By examining the interplay of regulatory frameworks, market conditions, and managerial practices, the study identified key drivers and barriers to success in this industry. It is recommended that future researchers adopt the strategies to further explore the complexities surrounding hedge funds and collective investment schemes. The findings of the study may aid in the development of future innovative product designs for financial intermediaries in the insurance sector.